2018
DOI: 10.3390/su10010126
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Evaluate Comprehensive Plan and Identify Priority Lands for Future Land Use Development to Conserve More Ecological Values

Abstract: Urbanization has significant impacts on the regional environmental quality through altering natural lands, converting them to urban built-up areas. One common strategy applied by urban planners to manage urbanization and preserve natural resources is to make a comprehensive plan and concentrate future land use in certain areas. However, in practice, planners used to make future land use planning mainly based on their subjective interpretations with limited ecological supporting evidence and analysis. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The InVEST model and its associated biophysical dataset were developed and calibrated by the Natural Capital Project in the Willamette Valley area within which Corvallis is located [17] and has been applied successfully in the other coastal areas in Western North America in previous studies [18,45,46]. This research uses the stormwater runoff yield and purification models and the biophysical data built in InVEST at 1 m × 1 m pixel resolution and combines the results at the parcel level.…”
Section: Stormwater Runoff Yield Modellingmentioning
confidence: 99%
“…The InVEST model and its associated biophysical dataset were developed and calibrated by the Natural Capital Project in the Willamette Valley area within which Corvallis is located [17] and has been applied successfully in the other coastal areas in Western North America in previous studies [18,45,46]. This research uses the stormwater runoff yield and purification models and the biophysical data built in InVEST at 1 m × 1 m pixel resolution and combines the results at the parcel level.…”
Section: Stormwater Runoff Yield Modellingmentioning
confidence: 99%
“…It is ranked as the third best small to medium suburban city to live in the U.S. in 2018 by Livability [2]. The State and City's planning system is considered to be very successful in the U.S. by policy-makers and planners in terms of directing urban growth into urban growth boundaries and conserving more ecological values [40,46]. The first parcel in the City was established in 1853, and by 2014, there had been nearly fourteen thousand parcels supporting 55,298 people [47].…”
Section: Study Areamentioning
confidence: 99%
“…The authors in [5] demonstrate that the urbanization process affects climate at all scales. Several studies have shown strategies to minimize the impact of growth and of urban density on climate using urban planning as a tool to control land usage and coverage, as well as reduce the impact of the urbanization process [6][7][8]16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The relation between the urbanization process and climate is complex.…”
Section: Urban Morphology and Climatementioning
confidence: 99%
“…Different methods and techniques exist to analyze urban morphological indices, ranging from the use of spatial metrics [31][32][33][34][42][43][44], as is the case of the present study, to the use of satellite images [45][46][47][48][49][50]. Several indices may be used in such analyses, such as aerodynamic roughness, porosity, building density, verticality, H/W ratio, and impervious surface fraction, helping to minimize the impacts caused by city growth.…”
Section: Urban Morphology Indicesmentioning
confidence: 99%